Direct Healthcare Cost of Fracture-related Infection Treatment - Nike Walter, MD; Ines Neubauer, MD; Susanne Baertl, MD; Volker Alt, MD; Markus Rupp, MD (JBJS Open Access)
Background:. Fracture-related infections (FRIs) pose significant clinical and economic challenges in trauma surgery. Despite advancements in treatment modalities, the economic burden of managing FRIs remains substantial. However, cost analyses are scarce. Therefore, the aim of this study was to analyze the direct healthcare costs associated with FRI treatment compared with initial fracture treatment across various fracture types in a level 1 trauma center in Germany. Methods:. A retrospective analysis of 95 patients treated for fractures and FRIs between 2013 and 2020 was conducted. Patients were categorized based on the fracture location: femur, tibia, ankle, and foot. Data collected included fracture characteristics, and costs related to both initial fracture treatment and FRI management. Costs were analyzed using diagnosis-related group (DRG) reimbursement data. The mean DRG reimbursement for initial fracture treatment and FRI treatment was compared to determine the economic impact of FRIs. Results:. The study revealed significant increases in costs for FRI treatment across all fracture types. For femur fractures, the mean reimbursement for initial treatment was €17,617.66, while FRI treatment costs were €31,731.49, resulting in a difference of €14,113.83 and a 1.8-fold increase in costs. Tibia fractures showed an increase from €10,327.70 to €28,024.38 (difference of €17,696.68, 2.7-fold increase of costs). Ankle fractures had a cost increase from €3,790.38 to €17,940.90 (difference of €14,150.52, 4.7-fold increase of costs), and foot fractures showed an increase from €6,557.95 to €23,272.48 (difference of €16,714.53, 3.5-fold increase of costs). Conclusions:. The costs for FRI treatment are substantially higher than those for initial fracture management across all fracture types studied. These findings emphasize the need for effective preventive measures and efficient management protocols to reduce the incidence and financial impact of FRIs. Level of Evidence:. Level III. See Instructions for Authors for a complete description of levels of evidence.